Nobody is protected: how the Border Patrol became the most dangerous police force in the United States - Jones, Reece (Counterpoint Press, 2022)
Introduction: Out of Control -- Part 1. The Wild West Origins of the Border Patrol. Send Two Coffins -- The Texas Rangers -- Closing the Back Gate -- They Have no Right to Go into the Interior -- Unreasonable Searches and Seizures -- Operation Wetback -- Part 2. The Supreme Court. Law and Order -- Terrorists in Suits -- Change of Heart -- Rank Racism -- Mexican Haircuts -- A Sixth Sense -- Free to Stop Any and All Motorists -- Part 3. The One Hundred Mile Zone. America's Frontline -- Hostile Terrain -- Checkpoint Nation -- Somebody Speaking Spanish -- The Everywhere Border -- Conclusion.